Absent Presence: an exploration of memory and family through printmaking - Hambsch, Oliver (Michaelis School of Fine Art, 2023)
Visual and linguistic metaphors help to conceptualise memory by reducing its physiological and philosophical complexities to a degree that allows its processes to be easily understood. Two commonly used metaphors are ‘memory as an imprint' and ‘memory as a photograph'. However, these metaphors ignore vital aspects of memory, such as its fluidity, the interplay between remembering and forgetting, and the role of imagination. They can thus be considered misleading and problematic. Of particular interest is the ‘memory-as-imprint' analogy and how engagement with the visual language of printmaking can modify it to create a more comprehensive depiction that accounts for the physiological processes of individual memory and the retention and transmission of collective, familial memory. Through my practical work, I seek to address these concerns through both traditional and experimental printmaking techniques, which I reflect on and analyse through the theoretical framework of printmaking. I use photographs sourced from my family archive as references, focusing in particular on those from the German post-war period, and remediate them into various print mediums, each addressing particular facets of memory that I consider important. My work is intended to serve as a reflection on what memory is and how it is experienced, the theoretical aspects of printmaking and my own relationship with my family memory. I argue that through a conceptual engagement with printmaking, print can be used as a metaphorical device that extends beyond the simple ‘memory-as-imprint' analogy.